Active play exercise intervention in children with asthma: a PILOT STUDY. Issue 1 (5th January 2016) - Westergren, Thomas; Fegran, Liv; Nilsen, Tonje; Haraldstad, Kristin; Kittang, Ole Bjørn; Berntsen, Sveinung
Abstract : Objective: Increased physical activity (PA) may be beneficial for children with asthma. Knowledge about how to intervene and encourage children with asthma to be physically active is required. In the present study, we aimed to pilot a 6-week exercise intervention designed as active play and examine attendance rate, exercise intensity and children's perceptions of participating. Methods: 6 children with asthma (4 boys, 2 girls) aged 10–12 years, participated in 60 min of active play exercise twice weekly. A mixed-methods design was applied. The data analysed included attendance rate, exercise intensity assessed by heart rate (HR) monitoring during exercise sessions, registration and description of the active play exercise programme, 3 semistructured focus groups, field observations of 5 exercise sessions, and preintervention and postintervention testing. Findings: The average attendance rate was 90%. Intensity ≥80% of maximal HR (HRmax ) was recorded for a median (IQR) time of 22 (8) out of 60 min per session. Median (IQR) HR during the sessions was 146 (9; 74% of HRmax ) bpm. Children reported increased health-related quality of life (HRQoL) post-test compared with baseline. Children enjoyed participating and reported no limitations by asthma or serious asthma attacks. Instead, they perceived that their asthma and fitness had improved after the programme. The instructors created an inclusive atmosphere that was characterised by easy-to-master games, fair competition, humour and mutual participation. Conclusions: The exercise intervention pilot focusing on active play had a high attendance rate, relatively high exercise intensity, and satisfaction; the children perceived that their fitness and asthma had improved, and reported increased HRQoL. A randomised controlled trial of active play exercise including children with asthma should be conducted to evaluate effect on PA level, physical fitness, asthma control and HRQoL.